Criminal Sanctions Fine For Corporations as Performers of Criminal Acts of Corruption From the Perspective of the Theory of Dignified Justice - Ismaidar Ismaidar; T. Riza Zarzani; Ongku Sapna Fella Hasibuan (International Journal of Law, Crime and Justice, 2024)
Korganization in nation building is very significant. Corporations can be said to be pillars of the nation's economy. Corporations are very influential not only on economic aspects, but also social, political and other aspects. As time goes by, crimes committed by corporations arise. The Criminal Code which does not recognize corporations as legal subjects opens up opportunities for individuals to take advantage of this legal loophole. The regulations governing corporate responsibility currently in effect are considered less effective and efficient. Provisions that clearly regulate "corporate criminal liability" are still at the Draft Criminal Code stage. Based on the research results, it was found that the corporate responsibility system has several doctrines or theories in determining responsibility. These theories include "identification doctrine, aggregation doctrine, reactive corporate fault, strict liability and vicarious liability." This research aims to increase knowledge regarding criminal responsibility by corporations. This research supports the immediate ratification of the Draft Criminal Code as an answer to legal problems regarding criminal acts committed by corporations. The method used in this research is normative juridical, with data collection techniques namely literature study. The data obtained in this research comes from writings or scientific works in the form of books, journals, dissertations and other literature.